To risk it all : General Forbes, the capture of Fort Duquesne, and the course of empire in the Ohio country - McConnell, Michael N. (Michael Norman) (Book collections on Project MUSE., 2020)
"General John Forbes's campaign against Fort Duquesne was the largest over-land expedition during the Seven Years' War in America. While most histories of the time period include the Forbes Campaign as an aside, McConnell documents how and why Forbes and his army succeeded, and what his success meant to the subsequent history of the mid-Atlantic colonies, native inhabitants of the Ohio Country, and the empire he represented. A close look at the Forbes Campaign and its personnel reveals much about both British relations with native peoples and the nature of Britain's American empire during a time of stress. Unlike other campaigns, this one was composed largely of colonial-not professional British-troops. In addition, individual colonies negotiated their role in the campaign and frequently placed their own local interests ahead of those of the empire as a whole. The campaign thus suggests the limits of imperial power and how Britain's hold over its American frontiers was, at best, tenuous and helped lead to an eventual break-down of empire in the 1760s and 1770s."--